2019
DOI: 10.5961/jhes.2019.356
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing learning outcomes in a materials science & nano engineering curriculum

Abstract: Açık ve ölçülebilir öğrenme çıktıları eğitim programlarının temelini oluşturmaktadır. Mühendislik eğitiminde öğretim sürecinin başarı ile sonuçlandırılması büyük ölçüde iyi yapılandırılmış öğrenme çıktılarına (kazanımlara) bağlıdır. Bu çalışmada Türkiye'deki özel bir üniversitenin mühendislik fakültesi malzeme bilimi ve nano mühendislik bölümü programındaki 41 derse ait 324 kazanım yapı bakımından incelendi ve iyi yapılandırılmış kazanımlar revize edilmiş Bloom taksonomisine göre sınıflandırıldı. Araştırmada n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…As the engineering profession requires the application of scientific principles for practical uses, the share of the apply dimension is expected to be greater. Yolcu [27] analyzed the verbs in learning outcomes of the Material Science and Nano Engineering curriculum and found apply and remember as the most common dimensions. Swart and Daneti [28] analyzed the Electronic fundamental learning outcomes and found that two lower levels of Bloom's taxonomy had the majority (58%) in both universities in Romania and South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…As the engineering profession requires the application of scientific principles for practical uses, the share of the apply dimension is expected to be greater. Yolcu [27] analyzed the verbs in learning outcomes of the Material Science and Nano Engineering curriculum and found apply and remember as the most common dimensions. Swart and Daneti [28] analyzed the Electronic fundamental learning outcomes and found that two lower levels of Bloom's taxonomy had the majority (58%) in both universities in Romania and South Africa.…”
Section: Discussionmentioning
confidence: 99%